Increased frontal lobe phosphocreatine levels observed in heavy cocaine users after treatment for cocaine dependence – An 1H MRS T2 relaxometry study. Issue 2 (2003) - Ke Ke, Y. Y.; Streeter Streeter, C. C.; Lowen Lowen, S. S.; Nassar Nassar, L. E. L. E.; Parow Parow, A. M. A. M.; Hennen Hennen, J. J.; Yurglun-Todd Yurglun-Todd, D. A. D. A.; Sarid-Segal Sarid-Segal, O. O.; Awad Awad, L. A. L. A.; Rendall Rendall, M. M.; Gruber Gruber, S. A. S. A.; Nason Nason, A. A.; et al.
Abstract : We have recently reported that relative concentrations of phosphocreatine (PCr) and creatine (Cr) may be estimated from brain 1H MR spectra based upon T 2 relaxation times. Emission tomography studies have consistently associated cocaine dependence and abstinence with decreased cerebral metabolism. We hypothesized that increased frontal lobe PCr levels would accompany treatment for cocaine dependence. Twenty-four cocaine dependent (CD) subjects were studied before and after 8 weeks of cocaine dependence treatment. Nine comparison subjects were studied at the same time points. At baseline, left frontal lobe ratios of PCr/tCr were 0.406±0.081 in CD subjects and 0.411±0.016 in comparison subjects. After treatment, these ratios increased 14.3% (0.464 vs. 0.406; p = 0.006) in CD subjects, remaining unchanged in comparison subjects (2.9%, 0.399 vs. 0.411; p = 0.480). At baseline, PCr levels of non‒responders were 17.8% lower (0.375 vs. 0.442; p = 0.042) than those of responders, defined as 25% decrease in urine cocaine metabolites. After treatment, CD subjects had increased PCr levels: 18.4% (0.444 vs. 0.375; p = 0.035) for non-responders and 10.4% (0.488 vs. 0.442; p = 0.092) for responders. These results are consistent with decreased cerebral metabolism during treatment, measured as increased PCr. This is the first report using 1 H MRS T 2 relaxometry to measure a change in human brain energetics.